Influence of Replacement of Concentrate with Enzose (Corn Dextrose) and Corn Steep Liquor on Nutrient intake in Nili Ravi Buffalo Bulls - M. ul Hassan; M. Sarwar; M. Mushtaq; M. ur Nisa; S. Khanum (Italian Journal of Animal Science, 2010)
The objective of the study was to examine the influence of replacement of concentrate with EZ and CSL on nutrient intake in ruminally cannulated buffalo bulls fed corncobs based diets. Diets were iso-nitrogenous and iso-caloric. The control diet (C) was contained 70% corncobs and 30 % concentrate on dry matter basis. Enzose and corn steep liquor replaced 100 % concentrates in respective diets (EZ and CSL) on dry matter basis. In the EZCSL diet, 100% concentrates was replaced by the blend of equal amount of CSL and EZ. Four buffalo bulls of almost same age and weight were fed twice a day at restricted intake (1.5% of their body weight) and at ad libitum intake in a replicated 4 x 4 Latin square. Dry matter, organic matter, crude protein, neutral detergent fiber and acid detergent fiber intakes were noticed non-significant in buffalo bulls fed C, EZ, CSL and EZCSL at both restricted and ad libitum intakes. EZ and CSL can safely replace the concentrate portion in corncobs based diets without affecting intake. In conclusion, EZ and CSL can be a good substitute of concentrate in corncobs based diets when fed at maintenance level.